2013
DOI: 10.15517/rbt.v57i1-2.11316
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and aboveground biomass of lianas in the tropical seasonal rain forests of Xishuangbanna, SW China

Abstract: Abstract:Lianas are important components of tropical forests and have significant impacts on the diversity, structure and dynamics of tropical forests. The present study documented the liana flora in a Chinese tropical region. Species richness, abundance, size-class distribution and spatial patterns of lianas were investigated in three 1-ha plots in tropical seasonal rain forests in Xishuangbanna, SW China. All lianas with ≥ 2 cm diameter at breast height (dbh) were measured, tagged and identified. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…For instance, in the Bobiri Forest Reserve, Ghana, a total of 27 species (≈18 species/ha) was recorded [17] whereas a much lower species richness (27 species ≈ 9 species/ha) was reported in the Tinte Bepo Forest Reserve, Ghana [15]. Moreover, liana species richness in this study was higher than those reported from outside Ghana: 51 species/ha in Bolivia [28] and 44 species/ha in China [29]. A similar trend was observed with regard to liana abundance.…”
Section: Discussioncontrasting
confidence: 68%
“…For instance, in the Bobiri Forest Reserve, Ghana, a total of 27 species (≈18 species/ha) was recorded [17] whereas a much lower species richness (27 species ≈ 9 species/ha) was reported in the Tinte Bepo Forest Reserve, Ghana [15]. Moreover, liana species richness in this study was higher than those reported from outside Ghana: 51 species/ha in Bolivia [28] and 44 species/ha in China [29]. A similar trend was observed with regard to liana abundance.…”
Section: Discussioncontrasting
confidence: 68%
“…Liana growth is strongly correlated with the diameter increment [48][49][50]. We, therefore, used the increment rate of the diameter to estimate the relative growth rate of lianas.…”
Section: Relative Growth Rate Of Lianasmentioning
confidence: 99%
“…In addition, because the pantropical equations consist mostly of data from the Neotropics and no data from Africa, we also estimated liana AGB using several regional allometric equations based on data from South Asia (Southern China: CH; Lü et al . ) and Malaysia (MY; Addo‐Fordjour & Rahmad ) and West African tropical forest (Ghana: GH; Addo‐Fordjour & Rahmad ) for comparison. CH represents 25 liana individuals ≥2 cm diameter that were harvested from undisturbed old growth forest in south central China ( R 2 = 0.870).…”
Section: Liana Aboveground Biomass (Agb) Allometric Equations Used Fomentioning
confidence: 99%
“…, Lü et al . , Addo‐Fordjour & Rahmad ). Although large lianas (>10 cm D 130 ) are less numerous than small lianas, large lianas contribute a disproportionately large amount of liana biomass (estimated to be 41% of total liana AGB (Phillips et al .…”
Section: Liana Aboveground Biomass (Agb) Allometric Equations Used Fomentioning
confidence: 99%